Step-by-step explanation
- Given the system of equations.
![\begin{cases} x - y = - 2 \\ 4x - y = 4 \end{cases}](https://img.qammunity.org/2022/formulas/mathematics/high-school/3rhxabh6l2vlr62gfxhog2f661fn3cs3e4.png)
- Use the elimination method as it is faster. We have to eliminate the y-term. (You can eliminate the x-term but it takes longer than eliminating y-term.)
Simply multiply the negative one in one of the equations.
![\begin{cases} - x + y = 2 \\ 4x - y = 4 \end{cases}](https://img.qammunity.org/2022/formulas/mathematics/high-school/bkvxgjtqtjb40wgz92btg6tg5xs4416p4h.png)
We can finally eliminate the y-term by adding both equations.
![( - x + 4x) + (y - y) = 2 + 4 \\ 3x + 0 = 6 \\ 3x = 6 \\ x = ( 6 )/(3) \longrightarrow \frac{ \cancel{6}}{ \cancel{3}} = 2 \\ x = 2](https://img.qammunity.org/2022/formulas/mathematics/high-school/aw72w2l1h81m1dsfxfkhdpbnu94dgpmovg.png)
- Substitute the value of x in any given equations. I will substitute in the first equation.
![x - y = - 2 \\ 2 - y = - 2 \\ 2 + 2 = y \\ 4 = y](https://img.qammunity.org/2022/formulas/mathematics/high-school/c9tpjnxkghtxvk9dbra35x9vjwb944mpwc.png)
- Check the answer by substituting the value of x and y in both equations.
First Equation
![x - y = - 2 \\ 2 - 4 = - 2 \\ - 2 = - 2 \longrightarrow \sf{true} \: \: \green{ \checkmark}](https://img.qammunity.org/2022/formulas/mathematics/high-school/26xllqikrmn5xufbmgeb0etjtj5ldms0na.png)
Second Equation
![4x - y = 4 \\ 4(2) - 4 = 4 \\ 8 - 4 = 4 \\ 4 = 4 \longrightarrow \sf{true} \: \: \green{ \checkmark}](https://img.qammunity.org/2022/formulas/mathematics/high-school/venhl7nipof1o7vd2xik2f3xp1pw7n4of3.png)
Hence, the solution is (2,4).
Answer
![\begin{cases} x = 2 \\ y = 4 \end{cases}](https://img.qammunity.org/2022/formulas/mathematics/high-school/kzvuboyuyp433xr7sfuw6u97y6dtgfh33q.png)
Coordinate Form
![(2,4)](https://img.qammunity.org/2022/formulas/mathematics/high-school/38ncp4hrqfsp630elj8qgt9rttb8uc5hn8.png)